2021
DOI: 10.7759/cureus.18912
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Findings in Renal Patients: A Single Renal Specialist Center Experience

Abstract: This study evaluated the importance of bone marrow aspiration and trephine biopsy (BM) for the diagnosis of underlying hematological abnormalities in renal patients. MethodsThis cross-sectional study on BM was carried out between August 2010 and April 2019, in our specialist renal center for various unexplained hematological abnormalities in patients with renal diseases [chronic kidney disease (CKD), end-stage renal disease (ESRD) requiring maintenance hemodialysis (MHD), patients with normal renal function bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…definition of bone marrow cellularity used in the current study: Specifically, hypercellular marrow is characterised by the presence of more than 70% cellular elements, normocellular marrow contains between 30% and 70% cellular elements, and hypocellular marrow is defined as containing less than 30% cellular elements [11,12]. For the present study, we investigated haematological parameters and morphological changes observed in the bone marrow of patients with CKD.…”
Section: Methodsmentioning
confidence: 99%
“…definition of bone marrow cellularity used in the current study: Specifically, hypercellular marrow is characterised by the presence of more than 70% cellular elements, normocellular marrow contains between 30% and 70% cellular elements, and hypocellular marrow is defined as containing less than 30% cellular elements [11,12]. For the present study, we investigated haematological parameters and morphological changes observed in the bone marrow of patients with CKD.…”
Section: Methodsmentioning
confidence: 99%